Thymic selection can compensate for mutations affecting T cell activation and generate a normal T cell repertoire in mutant mice - Kissler, Stephan (National Academy of Sciences, 2004)
Thymic selection adjusts the reactivity of the peripheral T cell repertoire to maximize recognition of pathogens and minimize stimulation by innocuous substances and self-antigen. The study of molecules implicated in T cell activation often involves the generation of knockout (-/-) mice. In many instances, knockout animals display revealing phenotypes. But should a lack of phenotype be interpreted as a lack of function? Bcl-xγ was shown previously to affect T cell activation in vitro, and here we note that overexpression of this molecule increases cell cycling after T cell receptor ligation by antibody. It was therefore surprising that Bcl-xγ(-/-), Bcl-xγ transgenic, and WT T cells displayed similar levels of sensitivity to antigen according to ex vivo stimulation. Bcl-xγ could be demonstrated to influence competitiveness and selection of thymocytes in a manner that counteracted the effects of Bcl-xγ mutation on T cell activation. These findings suggest that thymic selection can overcome genetic defects in T cell activation to generate a T cell repertoire of normal reactivity.